Evolution , legal and regulatory issues, and dispute resolution in the modern Islamic banking industry in Sri Lanka - Nafees, Seeni Mohamed Mohamed (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2011)
The foundation of the Islamic banking industry, which was laid during the time of the Prophet Muhammad (pbuh), began to evolve into an organised banking system in the twentieth century. It has been expanding around the globe and at present is emerging as a viable alternative system of banking to its Western counterpart. The Islamic banking industry has also reached Sri Lanka, which is among a few non-Islamic jurisdictions where legislation on Islamic banking has been introduced. In order to evaluate the industry in the country, this study is conducted. For this purpose, a qualitative method of research is adopted and personal interviews are also conducted with industry players and Nulame to provide more strength and depth to the study. In line with this, various libraries are utilised where books, journals, articles, cases and electronic sources retrieved through online database are referred. Furthermore, the United Kingdom and Bahrain ere also included in the study in order to see how the industry is operated in different jurisdictions and such a focus is expected to be beneficial to a developing non-Muslim country such as Sri Lanka. It is remarkable that these jurisdictions, the United Kingdom and Bahrain, are recognised as gateways to Islamic banking in Europe and the Middle Eastern region respectively. Consequently, the study found that basically there are no hurdles in the way of implementing Islamic banking in Sri Lanka. Similarly, it is concluded that there are no impediments in marketing the Islamic banking products such as mudarabah, murabahah, ijarah and musharakah. However, in order to provide a level playing field to the Islamic banking industry, there are a number of legal arrangements and amendments in terms of regulation which must be made available in due course. Thus, the legislation pertaining to, inter alia, corporate tax, stamp duty, means of dispute resolution and licensing procedures is to be made more conducive to the industry. The role of the Shareeah in the regulation of the industry must also be duly recognised. Finally, it is concluded that if all the suggestions and recommendations proposed by the study are properly incorporated into the legislation of Sri Lanka, it will certainly help the Islamic banking industry in the country to grow fast and emerge as an Islamic banking hub in the South Asian region as Malaysia and Bahrain where comprehensive legislation on Islamic banking has been introduced.